2018
DOI: 10.1042/cs20171280
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pulsatility in patients with cerebral small vessel disease: a systematic review

Abstract: Growing evidence suggests that increased intracranial pulsatility is associated with cerebral small vessel disease (SVD). We systematically reviewed papers that assessed intracranial pulsatility in subjects with SVD. We included 27 cross-sectional studies (=3356): 20 used Doppler ultrasound and 7 used phase-contrast MRI. Most studies measured pulsatility in the internal carotid or middle cerebral arteries (ICA, MCA), whereas few assessed veins or cerebrospinal fluid (CSF). Methods to reduce bias and risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 55 publications
6
60
0
Order By: Relevance
“…They observed that the elevated pulsatility index obtained in the middle cerebral artery was significantly correlated with severe WMHs, using the Fazekas scale. They confirmed the growing evidence supporting the association between increased intracranial pulsatility and cerebral small vessel disease 24 .…”
supporting
confidence: 76%
“…They observed that the elevated pulsatility index obtained in the middle cerebral artery was significantly correlated with severe WMHs, using the Fazekas scale. They confirmed the growing evidence supporting the association between increased intracranial pulsatility and cerebral small vessel disease 24 .…”
supporting
confidence: 76%
“…[12][13][14] However, in these studies, pulsatility was assessed in one (or at most two) main cerebral arteries by ultrasound. 15 Very few studies assessed pulsatility in the arteries, veins and CSF contemporaneously in the same subjects, 16 limiting the clinical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, so far, no clinical studies have measured cranial vascular pulsatility and PVS visibility. 15 Pulse-gated phase-contrast MRI is able to detect flow and pulsatility in major cerebral vessels and CSF spaces.…”
Section: Introductionmentioning
confidence: 99%
“…aqueduct, foramen magnum) within one examination, concurrently with CVR, making it possible to assess relationships between CVR, CBF and pulsatility directly. However, there are very few studies of intracranial pulsatility assessed with MRI in ageing or SVD(19) and no studies in humans of CVR assessed concurrently with intracranial vascular pulsatility, CSF flow dynamics, or resting CBF, to provide a complete assessment of intracranial haemodynamics.…”
Section: Introductionmentioning
confidence: 99%